A new nanohybrid for electrochemical removal of humic acids and Cr(VI). (26th August 2019) - Sarno, Maria; Scudieri, Carmela; Ponticorvo, Eleonora
Abstract: A new nanohybrid, based on flower‐like AuPtPd‐Fe3 O4, has been designed and prepared through an easy and scalable synthetic approach for the effective and simultaneous removal of humic acids (HAs) and Cr(VI). The nanocatalyst, prepared in a one‐step procedure, consists of nanoparticles with a grain size of about 40 nm, constituted of a magnetite core ca. 20 nm and petals of PtPd and Au and, after a ligand exchange process, results dispersible in water. Calibration equations were plotted for the removal evaluation in water samples. Electrochemical tests were carried out at pH 3.0 and 30 mA. HAs were highly mineralized with TOC removal efficiency of 95% after only 3‐h electrolysis, while 99% of total chromium (Cr) was removed in 3 h. A mechanism was proposed to describe the catalyst activity. The nanocatalyst shows high removal performances for HAs and Cr(VI) even after 10 times treatment, indicating good stability.